Development and pharmacological evaluation of vancomycin loaded chitosan films. (15th March 2021) - Kausar, Rabyya; Khan, Arif-ullah; Jamil, Bushra; Shahzad, Yasser; ul-Haq, Ihsan
Highlights: Vancomycin loaded chitosan film (VCF 2) fabricated by solvent extraction method. Anti-bacterial and characteristic properties of VCF2 was evaluated. VCF2 exhibited potential effect on oxidative stress markers. Angiogenesis, granulation tissue and epidermal regeneration promoted by VCF2. VCF2 showed down regulation in the expression of inflammatory markers. Abstract: Burn injuries are the most prevalent and devastating form of skin trauma. Current study aimed to fabricate novel chitosan-based composite films of vancomycin for wound healing applications. The developed vancomycin-chitosan films were evaluated for various quality attributes and were subjected to anti-bacterial activity against methicillin resistant Staphylococcus aureus (MRSA) and wound healing efficacy study in rat model. The prepared vancomycin-chitosan film 2 (VCF2) physically displayed a substantial tensile strength and swelling ratio. Pharmacologically, VCF2 exhibited sustained vancomycin release, excellent antibacterial activity and improved wound healing efficacy in rats. The superior wound healing potential was ascribed to the enhanced levels of reduced glutathione, glutathione-S-transferase, catalase and decreased lipid peroxidation. Furthermore, improved angiogenesis, granulation, epidermal regeneration and down regulation in the expressions of tumor necrosis factor, cyclooxygenase-2 and nuclear factor kappa B were the reasons of improved wound healing as confirmed by histopathological and molecular techniques. Thus, it is plausible to say that VCF2 could provide a potential therapeutic approach in burn wounds.